Analysis of Temporary Employment Company Business Environment - Meškienė, Erika; Tamošiūnas, Teodoras (Socialiniai tyrimai, 2019)
The relevance of the research. The emergence of temporary employment as an atypical form of work organization has become a relevant topic in the research of human resource management processes. Researchers analyze temporary employment not only as an atypical form of work organization, but also note that its practical use in labour market is characterized by flexibility while integrating workers into labour market and improving the productivity of the companies. The problem of the research. There is the lack of research and findings in scientific literature on temporary employment companies, empowering to reveal the flexibility of temporary employment management, its improvement and factors affecting it. There is little discussion among researchers about temporary employment as a flexible form of work organization, the tripartite relationship between a temporary employee, a temporary employment company and a user of temporary work. Specific and narrow issues are most often analysed. The description of the problem in this article can be summarized by the following problematic question: What are the factors that influence the management of a temporary employment company? Object of the research: factors that influence the management of a temporary employment company. Aim of the research: to disclose the factors determining the management of the activities of a temporary employment company. Research methods: Focus group, analysis of scientific literature, systematization, generalization and comparison, analysis of the contents of legal acts, statistics and other documents, methods of deduction and theoretical modelling, analysis, comparison and generalization of scientific statements and empirical research findings based on them, presentation of interpretations. Temporary employment is one of the forms of precarious employment and non-standard employment relationships. Unconventional employment patterns, in particular short-term and temporary work, have spread in many countries over the last few decades, but there is no universally accepted definition of temporary employment in scientific literature, as each country sets up their own specific regulation of employment. Temporary workers are usually considered to be workers who have concluded employment contracts for a specific period or for specific jobs, or those who have seasonal, casual or occasional work. It is widely recognized that temporary work improves the flexibility of labour market, has a positive economic impact, reduces unemployment and rapidly addresses temporary human resource shortages in companies. The form of temporary employment is convenient for disabled people, people with children and students for flexible integration into labour market, as it allows to take into consideration the mutual interests of the company and the temporary worker. Temporary employment services are provided by companies and agencies officially registered for these activities, which include the following functions: search and selection of employees, employee work accounting, employment contracts, etc. In Lithuania, the activities of temporary employment companies are regulated by the Labour Code of the Republic of Lithuania, and the criteria evaluation system of temporary employment companies is used to evaluate the activities of temporary employment companies. Every year, a temporary employment company has to submit a notice to the State Labour Inspectorate that it meets the established criteria. This article analyses a temporary employment company, coded as X at the request of its employees in order to maintain confidentiality. Information about the activities of this company in 2019 was provided by five company employees. The company has been providing temporary employment services in Northern Lithuania since 2012. The annual average number of temporary employees is about 70. The customers of the company – the users of temporary employment – are companies operating in manufacturing sector. The company establishes a tripartite employment relationship between a temporary employment user, a temporary employee and a temporary employment company, it employs a temporary employee and then sends an employee to work for a temporary employment beneficiary. The demand for services provided by Company X is determined by internal factors of collaboration with customers. Customers strive to minimize time and other resources and receive quality service. Manufacturing companies apply to Company X due to temporary increase in the scope of work, seasonality, sickness or holidays of employees. Company X expeditiously seeks the necessary employees for temporary employment in its existing database of job candidates or in labour market and then performs the necessary recruitment procedures. The company’s activities are strongly influenced by external factors: legislative system, economic and demographic situation of the country, unemployment rate, the education level of employed employees and qualification improvement system of the country. A probabilistic analysis of opportunities of Company X and their impact on its business has disclosed that there is a high probability that a company can attract more customers in the course of different events and that this would have a significant impact on the company’s business. The establishment of new divisions in other Lithuanian cities would also have a significant impact on this business, however, such establishment is unlikely. A probability analysis of threats and their impact on its business of Company X suggests that automation of workplaces for the company would be the factor that has the greatest negative impact on the company’s business, as it would reduce the need for temporary workers. New competitors, as a medium impact factor, have negative impact, however, due to the fact that the terms and conditions for engaging in these activities for temporary employment companies are high, the likelihood of this threat is low. The highest probability of threats is related to temporary workers, their experience, their qualifications and competencies, low motivation to work, low wages and the impact of emigration. There are five temporary employment companies operating in Šiauliai city and region. The analysis of the competitive environment of Company X revealed that the price of the service is the most important factor for success of five companies in Šiauliai city and region, as the importance of this factor was evaluated by high scores of 2-3,5 by competitors. This is followed by the available base of temporary staff, the image of the company in society and among customers. The timing of service orders is significantly more important to Company X than to other four companies, and conversely, the cost of temporary employment service is much more important to other four companies. In terms of competitiveness, Company X is the second of five companies. As the gap in the estimates of competitiveness is not large, it can be stated that all five temporary employment service companies operating in Šiauliai city and region are similarly competitive.